Pengaruh Produksi Kelapa Sawit Dan Tenaga Kerja Pada Pendapatan Tanaman Kelapa Sawit di Kecamatan Dendang Kabupaten Tanjung Jabung Timur - Joko Pangestu; Ery Bestary Al Haitamy; Ferdyan Wana Saputra (Journal of Applied Accounting And Business, 2025)
This study aims to determine how oil palm production and the amount of labor affect farmers' income in Dendang Sub-district. Oil palm production is the main factor that determines farmers' income, while labor helps in the production process. However, it is not yet known whether both actually affect farmers' income. For this reason, this study uses quantitative methods with multiple linear regression analysis to understand the relationship between production, labor, and farmers' income. The results show that oil palm production has a major influence on farmers' income. The more yields obtained, the higher the income received. In contrast, the amount of labor used does not have a significant influence on farmers' income. This means that the number of laborers working in the production process does not directly increase farmers' income. Based on the results of the study, increasing farmers' income in Dendang Sub-district should be focused on increasing oil palm production. Ways that can be done are by using better agricultural technology, superior seeds, and more effective cultivation methods. Thus, farmers can increase their yields without having to rely on more labor